Early induction versus expectant management in prelabour rupture of membranes - Gupta, Anjali; Gautam, Sarika; Prakash, Om; Chauhan, Meenakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Prelabour rupture of membrane defined as spontaneous rupture of membrane prior to the onset of regular uterine contractions. The incidence of PROM varies from 6-18%. Management of term PROM is not having specific guidelines leading to management dilemma. Methods: This prospective study was conducted on 100 women with singleton pregnancy, cephalic presentation with spontaneous PROM at term. The aim to compare maternal and perinatal outcome of early induction with expectant management in women with PROM. The patients were divided into two group expectant group and early induction group. Induction of labour was done by PGE2 gel and expectant group patient were observed for 24 hours for spontaneous labour since leaking. Augmentation of labour was done with Oxytocin if required. Outcomes were measured as PROM to delivery interval, induction to delivery interval, mode of delivery, maternal and neonatal morbidity. Results: Eighty percent of women of expectant group went into active labour within 24 hours, and all patient of induction group went into active labour in 18 hours (p<0.001). ROM to active labour interval and ROM to delivery interval were significantly less in early induction group, (9.87 and 17.212 hour) compared to expectant group (19.118 and 23.34-hour, p<0.001). Fetal distress and LSCS were comparatively higher in induction group (16%vs 2% p=0.038). Neonatal Sepsis was seen more in expectant group but statistically insignificant (22% versus 16%, p=0.26). Conclusions: Women with term PROM can be given informed choice of expectant management and early induction explaining the merits and demerits of both options.